Televisi dan Remaja: Implikasi Televisi pada Interaksi Sosial, Pembelajaran dan Politik Remaja - Nur Kumalasari; Niken Febrina Ernungtyas (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
This study examines the effects of television in adolescents, where television involves teens in their daily lives. The purpose of this study is to describe the effect of television and explain what influences television's influence on adolescents in Vocational High Schools. This type of research used in this research is descriptive quantitative, where the research method used in this study uses numerical based data and determines the population and sample. which is done by giving questions or an online questionnaire (questionnaire) to teenagers at SMK Ghama Caraka. Population criteria studied were adolescents aged 15-17 years. Respondents were asked as many as 30 people and taken using purposive sampling, namely the determination of sample techniques with certain considerations or with certain characteristics used with the questionnaire. Analysis of the data used in this research is to use descriptive statistics. This research data management uses SPSS 24 for windows to help analyze statistical data. And the results of this study prove that there is an influence of television on adolescents in SMK Ghama Caraka in social interaction, learning and politics in adolescents. Keywords: adolescents; effects; television